New insights regarding HCV-NS5A structure/function and indication of genotypic differences - Yamasaki, Lilian H. T. [UNESP]; Arcuri, Helen A.; Jardim, Ana Carolina G. [UNESP]; Bittar, Cintia [UNESP]; de Carvalho-Mello, Isabel Maria V. G.; Rahal, Paula [UNESP] (Biomed Central Ltd., 2012)
Background: HCV is prevalent throughout the world. It is a major cause of chronic liver disease. There is no effective vaccine and the most common therapy, based on Peginterferon, has a success rate of similar to 50%. The mechanisms underlying viral resistance have not been elucidated but it has been suggested that both host and virus contribute to therapy outcome. Non-structural 5A (NS5A) protein, a critical virus component, is involved in cellular and viral processes.Methods: The present study analyzed structural and functional features of 345 sequences of HCV-NS5A genotypes 1 or 3, using in silico tools.Results: There was residue type composition and secondary structure differences between the genotypes. In addition, second structural variance were statistical different for each response group in genotype 3. A motif search indicated conserved glycosylation, phosphorylation and myristoylation sites that could be important in structural stabilization and function. Furthermore, a highly conserved integrin ligation site was identified, and could be linked to nuclear forms of NS5A. ProtFun indicated NS5A to have diverse enzymatic and nonenzymatic activities, participating in a great range of cell functions, with statistical difference between genotypes.Conclusion: This study presents new insights into the HCV-NS5A. It is the first study that using bioinformatics tools, suggests differences between genotypes and response to therapy that can be related to NS5A protein features. Therefore, it emphasizes the importance of using bioinformatics tools in viral studies. Data acquired herein will aid in clarifying the structure/function of this protein and in the development of antiviral agents.
Keywords: Hepatitis C virus; Non-structural 5A protein; Bioinformatics; Genotype; Quasispecies; IFN response